Can secondary metabolites of plantain reduce N losses from urine patches?. Issue 1 (2nd January 2023) - Rodriguez, Maria J.; Navarrete, Soledad; Horne, Dave J.; Hanly, James A.; Bishop, Peter; Kemp, Peter D.
ABSTRACT: Plantain ( Plantago lanceolata L.) is a forage that produces secondary metabolites with one, aucubin, known to inhibit soil nitrification. This study aimed to quantify the exudation of aucubin and catalpol by plantain root systems in a hydroponic experiment; evaluate the effect of aucubin on nitrogen (N) leaching and nitrous oxide (N2 O) emissions from urine applied to plantain and ryegrass-white clover swards; and compare N losses from a ryegrass-white clover sward after urine from cows fed plantain and cows fed ryegrass-white clover was applied. Nitrate ( NO 3 − ) leaching and N2 O losses were measured in a lysimeter experiment. Catalpol, but not aucubin, was exudated by plantain roots. N2 O emissions were decreased by plantain swards and by ryegrass-white clover swards to which aucubin was also applied. Aucubin had no effect on NO 3 − leaching. Urine from cows grazing plantain had no effect on N2 O emissions, and N leaching when compared to the urine from cows grazing ryegrass-white clover with the same N content. We conclude the plantain sward and the aucubin applied to the ryegrass-white clover sward decreased N2 O emissions via mechanisms in the soil separate from the decreased emissions resulting from the lower N concentration of urine derived from cows grazing plantain.